Lasègue’s Sign - Kamath, Surendra Umesh (J Clin Diagn Res, 2017)
Lasègue’s sign is an interesting and important clinical sign in medicine for the last 150 years. The Lasègue test is commonly used in the physical examination of patients with low back pain. It is a test for lower lumbosacral nerve root irritation for example, due to disc prolapse. It is evident that the method of performance of this diagnostic sign varies with the physician. This article reviews the historical background and method of eliciting the sign.